Rancang Bangun Alat Pemberi Makan Ikan Menggunakan Blynk Untuk Keramba Jaring Apung Berbasis IoT - Laxsmy Devy (Teknik Elektro Politeknik Negeri Padang, 2021)
Research has been carried out on the Design of Fish Feeding Equipment for IoT-Based Floating Cages. The purpose of this study was to design a fish feeder for floating net cages using ESP-32 CAM, ultrasonic sensor, RTC module and servo motor. The research stages start from hardware design, software design, testing and analysis. The results showed that the RTC Module was functioning properly according to the Blynk Application Time Input Widget. A notification will be sent to the smartphone when the remaining volume of fish feed is less than 20%. ESP32-CAM can send images and stored on webhosting the results of the images displayed are affected by the signal speed. Overall the tool can function well. For further research, you can add a weight sensor to find out how much feed is given in each specified time.